Impact of changes in the IOC-MC asthma criteria: a British perspective. Issue 8 (1st August 2005) - Dickinson, J W; Whyte, G P; McConnell, A K; Harries, M G
Abstract : Background: Since 2001 the International Olympic Committee-Medical Commission (IOC-MC) has required athletes using inhaled β2 agonists to provide clinical evidence of their asthmatic condition. The aim of this study was to compare the reported prevalence of asthma at the 2000 and 2004 Olympic Games in the Great British Olympic team (Team GB). Methods: Following local ethics committee approval, 271 athletes (165 men) from the 2004 Team GB volunteered and provided written informed consent. An athlete was confirmed asthmatic if he or she had a positive bronchoprovocation or bronchodilator test as defined by the IOC-MC. Pre-Olympic medical forms from the 2000 Team GB were also examined to establish the prevalence of asthma among the members of Team GB at the 2000 Olympic Games. Results: The prevalence of asthma in the two teams at the 2000 and 2004 Olympic Games was similar (21.2% and 20.7%, respectively). In the 2004 Olympic Games 13 of 62 athletes (21.0%) with a previous diagnosis of asthma tested negative. A further seven with no previous diagnosis of asthma tested positive. Conclusions: The prevalence of asthma within Team GB remained unchanged between 2000 and 2004. The IOC-MC requirement that asthmatic athletes must submit documented evidence of asthma has highlighted that 13 (21.0%) previously diagnosed as asthmatic failed to demonstrate evidence of asthma while seven athletes with no previous history or diagnosis of asthma tested positive. Screening for asthma within elite athletic populations using bronchoprovocation challenges appears warranted to assist athletes in preparing more effectively for major sporting events.